Private-public partnership-produced urban space – An antithesis to ‘the right to the city’: A case study of Ruwa Town, Zimbabwe, from 1986-2021 - Terence Muzorewa (University of the Free State, 2023)
The article illustrates how the private-public-led urban development disenfranchised Ruwa residents’ rights to control the planning of their local environments and affordable access to basic public amenities and services in their town. Ruwa was one of the first postcolonial towns in Zimbabwe to emerge and develop using the private-public approach. The study uses Henri Lefebvre’s notion of the ‘right to the city’ as analytical lens. Lefebvre presents a vision for urban areas, in which residents manage urban space for themselves, beyond the control of private capital. In the same vein, this article argues that, although the private-public partnership approach was instrumental in the development of Ruwa Town, residents were left out of decision-making processes, yet they were the major stakeholders in the development process. Residents should take charge of development processes in their areas through grassroots participation. The study used mixed research tools which drew data from primary documents, statistical records, and interviews with various stakeholders of Ruwa Town development.